1991
DOI: 10.1002/jbt.2570060206
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐metabolizing enzymes in liver, olfactory, and respiratory epithelium of cattle

Abstract: The drug-metabolizing enzymes of olfactory and respiratory epithelium of cattle were determined. The data of nasal tissues were compared to those of bovine liver. Both oxidative and nonoxidative enzyme activities were investigated. Many compounds including testosterone were used as substrates for the P450-dependent monooxygenase activities. The results demonstrated that the P450 content and all the activities assayed including reduced nicotinamide adenine dinucleotide phosphate (NADPH)-cytochrome P450 reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 19 publications
4
47
0
Order By: Relevance
“…Microsomes were prepared from rat liver, kidney, lung and nasal mucosa as previously described (Menicagli et al 1994;Longo et al 1991) and were stored at À80°C. Protein content was assayed by the method of Lowry et al (1951).…”
Section: Methodsmentioning
confidence: 99%
“…Microsomes were prepared from rat liver, kidney, lung and nasal mucosa as previously described (Menicagli et al 1994;Longo et al 1991) and were stored at À80°C. Protein content was assayed by the method of Lowry et al (1951).…”
Section: Methodsmentioning
confidence: 99%
“…Testosterone hydroxylase was assayed as reported previously according to an HPLC method described by Platt et al [26], as previously reported [27]. Testosterone metabolites were resolved in a C18 RP Supelco column (250 × 4.6 mm) using an isocratic elution with methanol plus tetrahydrofuran (THF) 7.5% and H 2 O + THF 7.5% (27:73 v/v) for 8 min followed by a linear gradient reaching 42:58 v/v for 12 min and a final period of isocratic elution for further 10 min.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The fourth group of rats (controls) was treated with corn oil only. Microsomal and 100,000g supernatant fractions were prepared from the liver as previously described (Longo et al 1991).…”
Section: Animalsmentioning
confidence: 99%